(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Objective. To determine mortality trends from breast cancer in Mexico nationwide, by state, by socioeconomic region, and to establish an association between education, state of residence, and socioeconomic region with mortality from breast cancer in 2002–2011. Methods. Records of mortality associated with breast cancer were obtained. Rates of mortality nationwide, by state, and by socioeconomic region were calculated. The strength of association between states where women resided, socioeconomic regions, and education with mortality from breast cancer was determined. Results. Women who completed elementary school had a higher risk of dying from breast cancer than people with more education [relative risk (RR) 2.58, 95% confidence interval (CI) 2.49–2.67]. Mexico City had the strongest association with dying from breast cancer as state and as socioeconomic region 7 [Mexico City: RR 3.47, CI95% 2.7-4.46 (2002) and RR 3.33, CI95% 2.66-4.15 (2011) and region 7: RR 3.72, CI 95%: 3.15-4.38 (2002) and RR 2.87, CI 95%: 2.51-3.28 (2011)]. Conclusions. In Mexico, the raw mortality rates per 100 000 women who died from breast cancer increased. Mortality was higher in women who had elementary school than in those with more education. The strongest association was in Mexico City as state and as region 7.